GLORIOUS HISTORY OF THE ISLAMIC EDUCATIONAL INSTITUTE THE FATIMID DYNASTY IN EGYPT - Dhiyaa’ Ulfah; Juliani Damnur; Ellya Roza (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The Fatimid Dynasty (909–1171 AD) in Egypt marked one of the most important phases in the history of Islamic education. As a dynasty that embraced Ismaili Shi'ism, the Fatimids not only strengthened their political power, but also actively developed an education system as a means of spreading ideology and knowledge. One of their most monumental contributions was the establishment of Al-Azhar University in 970 AD, which initially functioned as a center for spreading Ismaili teachings, but later developed into an inclusive center of Islamic scholarship. The Fatimid government provided significant support for the development of educational institutions through funding, establishing libraries, and appointing prominent scholars as teachers. This article aims to historically examine the development and role of Islamic educational institutions during the Fatimid Dynasty and their contribution to the Islamic scholarly tradition. The method used is a literature study with a historical-critical approach to primary and secondary sources. The results of the study show that the Fatimid Dynasty succeeded in creating an organized education system that became a model for the development of Islamic educational institutions in subsequent periods.